1998
DOI: 10.1007/s001250051082
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of oxidative stress by oral N-acetyl-L-cysteine treatment decreases plasma soluble vascular cell adhesion molecule-1 concentrations in non-obese, non-dyslipidaemic, normotensive, patients with non-insulin-dependent diabetes

Abstract: To assess in vivo effects of antioxidants on vascular cell adhesion molecule (VCAM)-1 expression, circulating soluble VCAM-1 and intraerythrocytic reduced glutathione (GSH) and GSH disulphide (GSSG) concentrations were evaluated in non-insulin-dependent diabetic patients without complications (9 men, 6 women, 48 +/- 6 years old) before and after 1 month of either oral N-acetyl-L-cysteine (1.200 mg/day) or placebo treatments, given in randomized, cross-over, double-blind fashion. Ten healthy subjects (7 men, 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
51
0
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(58 citation statements)
references
References 20 publications
5
51
0
2
Order By: Relevance
“…The risk increase did not vary with time. In accordance with previous studies, we showed sVCAM-1 levels to be significantly associated with male sex, age, fasting insulin levels, vWF level, the presence of type 2 diabetes, hypertension, and microalbuminuria, and, inversely, with levels of total, LDL, and HDL cholesterol and estimates of glomerular filtration rate (18,(20)(21)(22)27,37). These variables, however, did not materially affect the association between sVCAM-1 levels and risk of cardiovascular mortality (Ta b l e 3).…”
Section: Discussionsupporting
confidence: 92%
“…The risk increase did not vary with time. In accordance with previous studies, we showed sVCAM-1 levels to be significantly associated with male sex, age, fasting insulin levels, vWF level, the presence of type 2 diabetes, hypertension, and microalbuminuria, and, inversely, with levels of total, LDL, and HDL cholesterol and estimates of glomerular filtration rate (18,(20)(21)(22)27,37). These variables, however, did not materially affect the association between sVCAM-1 levels and risk of cardiovascular mortality (Ta b l e 3).…”
Section: Discussionsupporting
confidence: 92%
“…Further, plasma soluble VCAM-1 negatively correlated with intraerythrocytic glutathione concentrations and decreased after N-acetyl-l-cysteine was given orally [8]. Therefore, the current findings support the previous hypothesis [8] that an early up regulation of VCAM-1 is present in non-insulin-dependent diabetic patients due to increased oxidative stress rather than hyperinsulinaemia.…”
Section: Discussionsupporting
confidence: 87%
“…Consistent with this interpretation, increased plasma soluble VCAM-1 concentrations, that were unrelated to fasting insulin concentrations, have already been described in noninsulin-dependent [8] and insulin-dependent diabetic patients [9]. Further, plasma soluble VCAM-1 negatively correlated with intraerythrocytic glutathione concentrations and decreased after N-acetyl-l-cysteine was given orally [8]. Therefore, the current findings support the previous hypothesis [8] that an early up regulation of VCAM-1 is present in non-insulin-dependent diabetic patients due to increased oxidative stress rather than hyperinsulinaemia.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Glycosylated hemoglobin concentrations are associated with reduced total plasma antioxidant trapping capacity in patients with type 2 diabetes (23), a finding consistent with the concept that clinically relevant hyperglycemia increases oxidative stress. However, antioxidant treatment (N-acetyl-L-cysteine) has decreased sVCAM-1 levels in one study (28), although it has not been possible to decrease sE-selectin or sVCAM-1 levels by tomato juice (29), ␣-tocopherol (29), or gliclazide (30). Because treatment of hyperglycemia has reduced sE-selectin levels in three studies (7,10; present study), it could be considered a better tool than antioxidants to lower sE-selectin concentrations in type 2 diabetes.…”
Section: Resultsmentioning
confidence: 88%